Interpretasi Mineralisasi Epitermal Berdasarkan Studi Ubahan Hidrotermal dan Tekstur Urat Kuarsa di Kawasan Hutan Lindung Taliwang, Nusa Tenggara Barat - Herman, Danny Zulkifli (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no3.20072Taliwang conservation forest, West Nusa Tenggara, is particularly covered by volcanic rocks consisting of alternated breccia and tuff. The breccia is composed of andesitic – dioritic clasts and matrix of fine-grained to lapilli tuff which had partially been hidrothermally altered and invaded by gold bearing quartz veins. Outcrops of quartz veins are commonly limonitized, trending nearly east-west and north-south with respectively dip of 70o and 85o. Identification of quartz veins originated from people mining’s waste leads to a prediction that there are quartz stockworks beneath the earth surface (50 – 100 m depth) in the conservation forest area, from which quartz veins penetrated the illite-paragonite-calcite-siderite- nacrite altered country rock. Textures of quartz veins were identified such as comb with some coarse- grained euhedral crystals, sugary/saccharoidal/fine grained crystalline quartz and ghost-bladed. Veins and host rocks generally contain disseminated and spotted pyrites. Evaluation of quartz textures, altered rocks analysis (PIMA method), fluid inclusion studies and chemical analysis (AAS method) of selective altered rocks/quartz vein samples exhibits that the alteration and mineralization processes might occur in an epithermal system, connecting with a change of hydrothermal fluids from near neutral into acid conditions at a temperature ranging from 231 to 185oC. Alteration of illite-paragonite-kalsit-siderite is suggested as a result of reaction between host rock and a near neutral fluid, whilst nacrite (kaolin group) or argillic is a result of reaction between host rock and an acid fluid, within a mixing zone of meteoric fluid and condensed acid gas released during boiling process of hydrothermal fluid in the depth. On the basis of salinity ranging from 0.9 to 2.2 equivalent wt.% NaCl of fluid inclusion, it is predicted that the deposition of gold bearing quartz and associated ore minerals takes place in a depth ranging from 293 to 120 m beneath paleosurface.